Elbow fistulas using autogeneous vein: patency rates and results of revision. Issue 922 (1st August 2002) - Murphy, G J; Saunders, R; Metcalfe, M; Nicholson, M L
Abstract : Background: The provision and maintenance of vascular access remains a major cost to end stage renal failure programmes. There are few reports regarding the surgical revision of the failing native elbow arteriovenous fistula (AVF). Patients and methods: A retrospective case note review was performed on all patients identified from the hospital vascular access database as having undergone construction of an autogeneous vein elbow AVF. Over a seven year period 282 autogeneous vein AVFs were fashioned in 232 patients using the brachial artery as the in-flow conduit. Of these 208 were brachiocephalic fistulas, or a variant thereof, and 74 were fashioned using the transposed autologous basilic vein (136 male: 96 female; median age 60 years, range 14–94 years). Results: Of 282 elbow fistulas 197 were successfully used for dialysis (70%). Cumulative primary patency of elbow fistulas using autogeneous vein in this series was 68%, 54%, and 44% at one, two, and three years respectively. A further 34 revision procedures were performed on 28 fistulas to maintain fistula function, and cumulative secondary patency after surgical revision was 75%, 60%, and 46% at one, two, and three years. Overall 21 out of 34 procedures (62%) successfully restored fistula function and cumulative primary patency of the revised fistulas was 56% at one year. Eighteen AVFs (brachiocephalic, n=12; autologous basilar vein, n=6) required revision for access dysfunction secondary to a short stenoses within 4 cm of the arteriovenous anastomoses. Of these 18 AVFs eight were revised by excision of the stenosed segment and either primary anastomoses of the two cut ends of arterialised vein or reanastomoses of the proximal venous limb proximally on the brachial artery. In another nine fistulas the excised segment was replaced with a short interposition graft (polytetrafluoroethylene, n=7; native basilic vein, n=1; bovine carotid artery, n=1). One fistula with postanastomotic stenoses and a more proximal needle site stenoses was revised using two vein patches. Overall 100% were patent at 24 hours, 13 provided successful dialysis (72%), and cumulative primary patency was 67% and 50% at six months and one year respectively. Conclusions: Successful surgical revision of failing native elbow fistulas can restore patency and improve cumulative secondary patency with potential benefits in terms of patient morbidity and mortality. These results compare favourably to published patency rates after fistula salvage using interventional radiological techniques.